Cloning and Sequencing cDNA Encoding for Rhoptry-2 Toxoplasma Gondii Tachyzoite Local Isolate - M. Murwantoko; Jaka Widada; Yani Lestari Nuraini (Indonesian Journal of Biotechnology, 2008)
Rhoptry protein belongs to an excretory and secretory antigens (ESAs) that play an important role during active penetration of parasite into the cell target. This protein an able Toxoplasma gondii to actively penetrate targeted cell, meanwhile ESAs protein stimulates intracellular vacuole modification. It is, therefore, after the parasite successfully enter the cell target then Granule (GRA) proteins are responsible for the formation of parasitophorus vacuole, which is protect the fusion with other intracellular compartments such as lysosomal vacuole. Consequently, this parasite is being able to survive and multiply at the cell target. The current study was aimed to clone and sequens cDNA encoding for ROP-2 of local isolated T. gondii tachizoite through DNA recombinant technique. Total ribonucleic acid (RNA) was isolated from tachyzoites of local isolated T. gondii that were grown up in Balb/c mice. Messenger RNA was isolated from total RNA using PolyAtract mRNA Isolation System. Messenger RNA was used as a template for synthesis cDNA using Riboclone cDNA Synthesis System AMV-RT. EcoRI adaptor from Riboclone EcoRI Adaptor Ligation System was added to Complementary DNA and than ligated to pUC19. Recombinant plasmid was transformed into E. coli (XL1-Blue). The transformed E. coli XL-1 Blue were plated on LB agar containing X-Gal, IPTG and ampicillin. Recombinant clones (white colony) were picked up and grown up in the LB medium at 37oC overnight. Expression of recombinant protein was analysed by immunoblotting in order to identify cDNA recombinant wich is express ESA of T. gondii local isolate. Recombinant plasmid were isolated using alkalilysis method and were elektroforated in 1% agarose gel. The isolated DNA recombinant plasmid was cut using Eco RI and then sequenced through Big Dye Terminator Mix AB1 377A Sequencer using M13 Forward and M13 Reverse primers. The conclusion of this results showed that the recombinant clone was coding for excretory and secretory protein which has molecular weight of 54 kDa. The DNA alignments of sequence from the cloned gene showed 97% homology with gene encoding for ROP-2 of T. gondii RH isolate.', 'string'),(99, 'en_US', 'subject', 'Toxoplasma gondii, tachizoite, ESA, complementary DNA, ROP2